El incremento de la población reclusa en España entre 1996- 2006: Diagnóstico y remedios - Cid Moliné, José (Revista Española de Investigación Criminológica, 2008)
In the years 2003 and 2004 a liberal Spanish association of criminal law professors and criminal judges (Grupo de Estudios de Política Criminal) made a paper proposing some reforms of the Spanish sentencing system. The proposal was based on a negative vision of the evolution of sentencing in Spain, which was blamed for the increase in incarceration rates since the implementation of the new criminal code of 1995. The present paper explores the reasons of the increase of the prison population from 1996 until 2006, analyses the capacity of the reductionist proposals made by this Spanish association to revert the trends and discus possible objections to this kind of policy.